Segmental and kinetic contributions in vertical jumps performed with and without an arm swing - Feltner, M. E.; Bishop, E. J.; Perez, C. M. (Research Quarterly for Exercise and Sport, 2004)
To determine the contributions of the motions of the body segments to the vertical ground reaction force (Fz), the joint torques produced by the leg muscles, and the time course of vertical velocity generation during a vertical jump, 15 men were videotaped performing countermovement vertical jumps from a force plate with and without an arm swing. Linear kinematic, Fz, and joint torque data were computed and compared using repeated measures analysis of variance. Maximum jump height was significantly larger in the arm swing jumps compared to the no arm swing jumps and was due to both a higher height of the center of mass (CM) at takeoff (54%) and a larger vertical velocity of the CM at takeoff (46%). The net vertical impulse created during the propulsive phase of the arm swing jumps was greater due to a trend of an increased duration (0.021 s) of the propulsive phase and not to larger average values of Fz. In the arm swing jumps, the arm motion resulted in the arms making a larger maximal contribution to Fz during the middle of the propulsive phase and decreased the negative contribution of the trunk-head and thigh to Fz late in the propulsive phase. Last, the arm swing decreased the extensor torques at the hip (13%), knee (10%), and ankle (10%) early in the propulsive phase but augmented these same extensor torques later in the propulsive phase.